Safety of MST in clinical application: a systematic review of randomized controlled studies - Jinling Cheng; Zhanxiang Lin; Zicai Liu; Dongmiao Han (Frontiers in Neurology)
BackgroundMagnetic seizure therapy (MST) is an innovative neurostimulation technique. While MST shares similarities with other neuromodulation techniques, such as electroconvulsive therapy (ECT) and transcranial magnetic stimulation (TMS), most research has predominantly focused on its efficacy. However, there is a notable scarcity of studies addressing MST’s safety. Therefore, the primary aim of this review is to synthesize the available safety data, contributing to a more balanced understanding of this promising treatment modality.MethodsEight databases (PubMed, Embase, Cochrane Library, Web of Science, CNKI, CBM, VIP, and Wanfang Data) were searched up to August 2024. The evaluation process was strictly adhered to by the Cochrane Risk of Bias assessment tool and RevMan 5.4.ResultsOf the 507 potential studies identified, after excluding duplicate studies, we reviewed the titles and abstracts of 217 studies, 149 of which were excluded. The full text of 68 studies was obtained and assessed against the inclusion and exclusion criteria, with 19 studies meeting the inclusion criteria. The therapeutic device and treatment parameters for MST are still being investigated, and the mechanism of MST is unclear, but there is almost consistent agreement on the efficacy and safety of MST.ConclusionThis study is the first systematic review of the safety of MST, and the findings suggest that MST can be used as an alternative treatment for certain psychiatric disorders with few side effects. Therefore, larger samples and more randomized controlled double-blind trials are needed in the future better to examine the clinical efficacy and safety of MST.